The condition and perspectives of poultry production development on municipality Lajkovac area - Cvijanović, Drago; Stojković, Aleksandar; Lang, Jelena (Economics of Agriculture, 2010)
The paper points out to a current state, perspectives and possibilities of poultry production development in municipality Lajkovac. It is separated in two parts: 1) Brief review of potential in agriculture and agriculture development level in area of Lajkovac municipality and 2) Poultry production in the Republic of Serbia and perspectives of this production development in Lajkovac municipality. In the first part is given the state review in agriculture of Lajkovac municipality, more accurate, a review of existing resources and level of agricultural development. In the second part, the accent was put on analysis of the state, i.e. on problems and perspectives of poultry products’ market development in the Republic of Serbia. In the second part is especially pointed out also to development possibilities of poultry production in the sector of individual agricultural producers, i.e. in cooperation with the firm "Vindija" Lajkovac.